Presença de trans-resveratrol em geléias de uva e sua relação com a radiação UV - Alves, Audrei de Oliveira (2006)
The presence of the composition trans-resveratrol (4,3',5'-trihidroxiestilbeno) was determined in grape jellies, with and without sugar, industrially produced in Brazil. Beyond this composition, also it has ben determined total phenols, total anthocyanins, total acidity, reducing sugars, soluble solids and color. Although in small concentrations, the presence of trans-resveratrol was positive in all the analyzed commercial jellies. At as a moment, an experiment with the objective was conducted to verify the increase in the concentration of trans-resveratrol in grape jellies, through treatment after-harvest of the grapes of cv. Isabel through irradiation with UV-C ultraviolet light and cooled atmosphere 0,5°C and posterior storage 20oC. The treatment of the grapes in such a way has made possible a significant increase in the concentration of trans-resveratrol in the berries as well as in the radiated clusters. From these radiated grapes, laboratorial production of jellies of grapes with and without sugar was made and submitted to the same analyses of the commercial jellies. These jellies had presented a considerable increase in the levels of trans-resveratrol, when compared with the commercial jellies. The jellies without sugar, due to its process of manufacture, had presented significant higher of this composition. In the sensorial analyses, the consumers did not identify the jellies of radiated grapes, have shown good acceptability, giving preference for its color, aroma and consistency. The results found for sensorial analyses are confirmed by physical-chemical analyses.